Mechanistic investigations of the asymmetric hydrosilylation of ketimines with trichlorosilane reveals a dual activation model and an organocatalyst with enhanced efficiency. Issue 11 (2nd March 2017) - Li, X.; Reeder, A. T.; Torri, F.; Adams, H.; Jones, S.
Abstract : Mechanistic investigations of a catalyst used for the asymmetric hydrosilylation have revealed a 'dual activation' model and catalyst that maintains its performance at 0.01 mol% loading. Abstract : Structural probes used to help elucidate mechanistic information of the organocatalyzed asymmetric ketimine hydrosilylation have revealed a new catalyst with unprecedented catalytic activity, maintaining adequate performance at 0.01 mol% loading. A new 'dual activation' model has been proposed that relies on the presence of both a Lewis basic and Brønsted acidic site within the catalyst architecture.